Progressive Legal Framework for the Regulation of Sexual Violence Crimes in Indonesia - Gusta Andini, Orin (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2023)
This article aims to describe the progressive legal dimension in regulating sexual violence crimes. The research method used is a normative research method with a statute approach and a conceptual approach. The results of the study show that the progressive legal dimension in the regulation of sexual violence crimes is reflected in the material criminal law which regulates forms of sexual violence in accordance with the times, as well as the formal criminal law relating to evidence. The legal dimension of progression in regulating criminal acts of sexual violence in Indonesia in Law Number 12 of 2022 concerning Crimes of Sexual Violence has uncovered the veil of law which so far has failed to achieve substantive justice because it is trapped in material and formal criminal law rules that are procedural and formalistic in nature. handling cases of sexual violence.